Alamelu Vairavan and Patricia Marquardt: Healthy South Indian Cooking - Jaine, Tom (Petits Propos Culinaires, 2024)
Alamelu Vairavan and Patricia Marquardt: Healthy South Indian Cooking: Hippocrene, 2001: ISBN 0-7818-0867-7: 348 pp., photos, h/b, 24.95.